Risks and tensions of collective trademarks and certificates of origin of collective indigenous handcrafted creations - Barrera Jurado, Gloria Stella; Pontificia Universidad Javeriana (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2014)
This study was carried out as part of the research process on the “Protection of collective indigenous handcrafted creations from a Human Rights perspective”. The aim of this research is to understand and interpret the dynamics of indigenous creations and possible ways to protect them. For a long time traditional indigenous knowledge wasof interest only to some intellectuals, artists and social scientists while for others it was invisible, disregarded and considered backward. Today this knowledge takes on a great value for several social actors as it is being considered a significant merchandise for commercial exploitation. At present there is a deep preoccupation for what we have called in this study the permitted appropriations and the non-permitted appropriations of these creations on the part of the Colombian State, enterprises, artists and designers. That is why in this study we approach two cases with an important media relevance. This analysis aroused more questions than answers.